ALANG SUNTIANG PANGULU DANCE: REGENERATION CRISIS IN CONTEMPORARY SOCIETY - Wahida Wahyuni; Zulfikar Rizki Ananda; Sri Meiweni Basra; Fattahul Anugraha; Donny Osmond (Pascasarjana Institut Seni Indonesia Padang Panjang, 2026)
Alang Suntiang Pangulu Dance is a ritual dance originating from the community of Nagari Padang Laweh, Agam Regency, West Sumatra, performed during the batagak pangulu ceremony or the inauguration of traditional clan leaders. Currently, the existence of this dance is facing a regeneration crisis caused by an exclusive and genealogically based cultural inheritance system. This study aims to analyze the regeneration crisis of Tari Alang Suntiang Pangulu within the dynamics of cultural transmission in contemporary Minangkabau society. The research employs a qualitative method with an ethnochoreological approach through literature studies and cultural phenomenon interpretation. The Cultural Transmission Theory proposed by Luigi Luca Cavalli-Sforza and Marcus W. Feldman is used as the analytical framework to examine vertical, horizontal, and oblique transmission patterns in sustaining the dance tradition. The findings reveal that the inheritance system of Tari Alang Suntiang Pangulu predominantly operates through vertical transmission within clan and traditional leadership structures. This closed transmission pattern limits regeneration and makes it difficult for the tradition to adapt to contemporary social changes. The regeneration crisis is further intensified by the declining interest of younger generations in ritual arts, the limited performance space, and the dominance of popular culture in modern society. This study argues that the primary issue surrounding Tari Alang Suntiang Pangulu lies not only in cultural preservation efforts but also in the stagnation of traditional cultural transmission systems that have yet to develop adaptive inheritance patterns in the modern era.